Factors that affecting nursing students quality of interpersonal relationships - Thais Josgrilberg Pereira; Jéssica Pereira Trentino; Francine da Costa Alves; Ana Cláudia Puggina (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Aims: to evaluate gender, age, undergraduate year, and grades affecting the quality of their interpersonal relationships of nursing students. Method: Cross-sectional quantitative study. We used characterization questionnaire and the Interpersonal Relationships Inventory - friendly version. Results: The sample was of 184 nursing students with an average age of 23.4 years old (± 5.3). There was a statistically significant difference in the sex comparison with the Support factor (p-value = 0.01) and with the Depth factor (p-value = 0.02). Conclusions: Scholar grades affecting the choice of friendships since most of them were due to similarity and did not interfere in the quality of relationships. The year in undergraduate program did not affect the quality of relationships.